2007
DOI: 10.1016/j.euje.2007.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer radial systolic strain can identify subendocardial ischemia: An experimental tissue Doppler imaging study of the porcine left ventricular wall

Abstract: Aims: This study investigates whether subendocardial ischemia can be detected by measuring multilayer radial systolic strain from epicardial tissue Doppler imaging. Methods:In 10 anesthetized open-chest pigs an extracorporeal shunt from the proximal brachiocephalic to the left anterior descending coronary artery was constricted in steps. Color microsphere injections and short axis Tissue Velocity Imaging (TVI) recordings were performed with open shunt, with a non-significant stenosis, and with 2 steps of shunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
3
19
0
3
Order By: Relevance
“…A non-significant coronary stenosis created in animal model, not altering the transmural flow distribution, induced an early decrease in subendocardial myocardium ε-radial and therefore in the gradient was also observed by tissue Doppler strain imaging [16]. As an angle-independent tool and a novel multi-layer approach, the 2D speckle tracking in the present study permitted the assessment of circumferential compression and confirmed its transmural heterogeneity with a higher ε-circum in the subendocardial than subepicardial myocardium layer.…”
Section: Transmural Heterogeneity Of Circumferential Strainmentioning
confidence: 68%
“…A non-significant coronary stenosis created in animal model, not altering the transmural flow distribution, induced an early decrease in subendocardial myocardium ε-radial and therefore in the gradient was also observed by tissue Doppler strain imaging [16]. As an angle-independent tool and a novel multi-layer approach, the 2D speckle tracking in the present study permitted the assessment of circumferential compression and confirmed its transmural heterogeneity with a higher ε-circum in the subendocardial than subepicardial myocardium layer.…”
Section: Transmural Heterogeneity Of Circumferential Strainmentioning
confidence: 68%
“…Again, peak systolic, end-systolic, and postsystolic strain were reported. Dimensions for ROIs and corresponding SL settings for the one-layer and three-layer radial TDI analysis were based on previous experience (20,21). The commercially available EchopacPC software uses a weighted linear regression of the velocities over the SL (10).…”
Section: Methodsmentioning
confidence: 99%
“…Reference values for the normal LV rotation gradient from apex to base using echocardiography are thus needed. Increased interest has recently been shown for myocardial multilayer strain measurements (2,3,6,14,21,27). In contrast with methods averaging strain over the wall, multilayer analysis allows for more layer-specific information regarding the functional state of myocardial fibers at different depths of the wall.…”
mentioning
confidence: 98%
“…The detailed transmural behavior of the heart wall deformation remains a matter of debate, with conflicting findings. Most studies report increasing radial strain from the epi-to the endo-cardium [1], but some show maximum strain at mid-myocardium [2]. Finite element models (FEM) of the left ventricle (LV) indicate that the transmural strain profiles may depend on local wall curvature, although this has not been demonstrated experimentally [3,4].The heart's motion is divided into a passive filling phase, diastole, and an active contraction phase, systole.…”
Section: Introductionmentioning
confidence: 99%